2019
DOI: 10.1101/816959
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A CTP-dependent gating mechanism enables ParB spreading on DNA

Abstract: The tripartite ParA-ParB-parS complex ensures faithful chromosome segregation in the majority of bacterial species. ParB nucleates on a centromere-like parS site and spreads to neighboring DNA to form a network of protein-DNA complexes. This nucleoprotein network interacts with ParA to partition the parS locus, hence the chromosome to each daughter cell. Here, we determine the cocrystal structure of a C-terminal domain truncated ParB-parS complex from Caulobacter crescentus, and show that its N-terminal domain… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 79 publications
(167 reference statements)
1
24
0
Order By: Relevance
“…The role of CTP binding and hydrolysis in ParB-driven partition complex formation was also shown for M. xanthus ParB [141]. Interestingly, in a recent study, Jalal and co-workers demonstrated that ParBs from various bacterial species show variation in their intrinsic capabilities for spreading and that the determinant of this variability maps to the N-terminal domain (NTD) [133]. The study used ChIP-seq to analyze ParB spreading in a heterologous host, so the results may not recapitulate all the determinants affecting the extent of spreading in its original host (like DNA supercoiling, involvement of other proteins).…”
Section: The Structure Of the Parb-pars Complexmentioning
confidence: 85%
See 3 more Smart Citations
“…The role of CTP binding and hydrolysis in ParB-driven partition complex formation was also shown for M. xanthus ParB [141]. Interestingly, in a recent study, Jalal and co-workers demonstrated that ParBs from various bacterial species show variation in their intrinsic capabilities for spreading and that the determinant of this variability maps to the N-terminal domain (NTD) [133]. The study used ChIP-seq to analyze ParB spreading in a heterologous host, so the results may not recapitulate all the determinants affecting the extent of spreading in its original host (like DNA supercoiling, involvement of other proteins).…”
Section: The Structure Of the Parb-pars Complexmentioning
confidence: 85%
“…All models postulate that multiple ParB-ParB interaction interfaces must be involved in the assembly of higher-order complexes. Structural studies have indeed demonstrated the flexibility of ParB molecules, the ability to bridge different parS sequences, as well as various cross-monomer interactions [115,116,122,133]. Notably, the majority of mutational analyses show that the conserved arginine patch residues are required for ParB spreading and DNA partition, thereby indicating the crucial role of this motif in ParB functions [68,114,127].…”
Section: The Structure Of the Parb-pars Complexmentioning
confidence: 99%
See 2 more Smart Citations
“…This bridging is mediated by dimerization of the arginine-rich ParB box II and was recently shown to be modulated by CTP binding in this region (Osorio-Valeriano et al, 2019;Soh et al, 2019). Notably, while in all bacterial species that use the parABS system, ParB specifically binds parS sequences, the affinity and specificity of ParB toward parS sequences vary among bacteria, resulting in differences in ParB spreading (Jalal et al, 2019). These differences, as well as variations in the number and distribution of parS sites, are reflected in the species-specific architecture of the ParB complex.…”
Section: The Role Of Para and Parb In Oric Segregationmentioning
confidence: 99%